Pengambilan Keputusan Dalam Peningkatan Mutu Pendidikan Islam di Madrasah - Erawadi, Erawadi; Simatupang, Longgasari; Sitorus, M Walimsah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Improvements to achieve quality education do not only fulfill the input and output aspects, but what is more important is the process aspect, which means decision making, program management, institutional management processes, teaching and learning processes and monitoring and evaluation processes with the note that The teaching and learning process has the highest level of importance compared to other processes. Apart from the problems above, the low quality of education covers the entire education system, especially the management system and work ethic, quality, quantity of teachers, curriculum and physical facilities and facilities. As a vicious circle where the position of the school is in a casual relationship, from inadequate funding, inadequate facilities, education as it is, low quality, lack of enthusiasm, low innovation, and lack of interest, and so on, it revolves like a vicious circle. What's even more ironic is that they always fight for positions, don't want to be led, and by nature they always want to lead, selfishly always want to win themselves, even though the reality is really wrong and not in accordance with the existing rules (statutes). And this is a fact that occurs in educational institutions, especially Islamic education.